MINCED MEAT SEMI-FINISHED PRODUCTS CONTAINING OILSEEDS - Samchenko O.N.; Merkucheva M.A. (Техника и технология пищевых производств)
One way to solve the problem of balancing the chemical composition of minced meat semi-finished products is the integrated use of raw materials of animal and vegetable origin. The purpose of the research is the development of formulations and determination of nutritional value of minced meat semi-finished products with oilseeds. The chemical composition of sesame seeds, sunflower seeds, and pumpkin seeds has been studied and the possibility of their use in the manufacture of semi-finished minced meats has been revealed. The formulae of minced meat semi-finished products, in terms of functional-technological and organoleptic properties, have been developed with optimum ratio of plant and animal components. Total organoleptic evaluation of the samples has shown a positive trend. Taste, smell, texture and overall evaluation have been improved. A slight reduction of the criterion for chemical composition of semi-finished products compared with that of a control sample has been found. It has been caused by the change of protein : fat : solids balance with the increase of vegetable fat and protein. The studied samples are characterized by a more balanced amino acid composition: the increase in SCOR and efficiency ratios is marked. The index of comparable redundancy is reduced, indicating a more complete use of the essential amino acids of minced meat semi-finished products for anabolic purposes. The developed samples meet the daily requirement for a number of essential nutrients by 11 - 64%. The content of vitamins A, B1 and E in the finished product containing sunflower seeds, that of magnesium and calcium in the sample containing sesame seeds, and 1.5 - 2 times increase of iron and zinc content enhance their nutritional value and allow classifying the samples as fortified foods.